Iterative Method for the Solution of Linear Equations with Restrictions - Kucheruk, T. A.; Luchka, A. Y. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We propose a new approach to the investigation of linear equations with restrictions. For the problem considered, we establish consistency conditions and justify the application of an iterative method.